Total Saponins of Aralia Elata (Miq) Seem Alleviate Calcium Homeostasis Imbalance and Endoplasmic Reticulum Stress-Related Apoptosis Induced by Myocardial Ischemia/Reperfusion Injury - Ruiying Wang; Minghua Yang; Min Wang; Xuesong Liu; Huibo Xu; Xudong Xu; Guibo Sun; Xiaobo Sun (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Total saponins of Aralia elata (Miq) Seem (AS) from the Chinese traditional herb Long ya Aralia chinensis L. reportedly provide cardioprotective effects, but the exact mechanisms require further study. Previous studies have showed that myocardial ischemia/ reperfusion injury (MIRI) was related to calcium homeostasis imbalance and endoplasmic reticulum stress (ERS). Thus, this study aimed to demonstrate protective effects of AS on MIRI. Methods: After administrating AS for 5 days, the left anterior descending artery coronary artery of Sprague-Dawley (SD) rats was ligated for 30 min. After 48 h of reperfusion, haemodynamics, Evans blue/ 2,3,5-triphenyltetrazolium chloride (TTC) staining, hematoxylin-eosin (HE) staining, masson staining and the levels of lactate dehydrogenase (LDH) and creatine kinase (CK), superoxide dismutase (SOD), malondialdehyde (MDA) were detected to assess MIRI. ATPase activity and Western Blot were used to study the mechanisms. Results: Compared with IR group, AS treatment groups could significantly reduce myocardial infarct size; improve myocardial pathologic progress; decrease content of LDH, CK, and MDA; increase content of SOD; and restore the activities of Ca2+-Mg2+-ATPase, Na+-K+-ATPase, sarcoplasmic reticulum Ca2+-ATPases (SERCA), and calcineurin (CaN). AS treatment groups also significantly up-regulated the expression of GRP78, C/EBP homologous protein (CHOP), and Bax, and down-regulated the expression of Bcl-2, all similar to the effects of ERS. Conclusion: These findings illustrated that AS could prevent myocardial ischemia/reperfusion injury and reduce calcium homeostasis imbalance and ERS-related apoptosis.